2007
DOI: 10.1093/ajcn/85.4.1142
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption, n−3 fatty acids, and subsequent 5-y cognitive decline in elderly men: the Zutphen Elderly Study

Abstract: A moderate intake of EPA+DHA may postpone cognitive decline in elderly men. Results from other studies are needed before definite conclusions about this association can be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
2
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(187 citation statements)
references
References 31 publications
5
170
2
10
Order By: Relevance
“…Neither of the two positive studies observed statistically significant inverse associations with dietary intake levels of the marine n-3 fatty acids (143,149) . However, of the six studies that measured biochemical levels of n-3 fatty acids, three observed statistically significant reductions in the rate of cognitive decline (83,86,150) and two others observed inverse associations with dementia (89,137) .…”
Section: Cardiovascular Mechanisms Of Fish Protectionmentioning
confidence: 82%
“…Neither of the two positive studies observed statistically significant inverse associations with dietary intake levels of the marine n-3 fatty acids (143,149) . However, of the six studies that measured biochemical levels of n-3 fatty acids, three observed statistically significant reductions in the rate of cognitive decline (83,86,150) and two others observed inverse associations with dementia (89,137) .…”
Section: Cardiovascular Mechanisms Of Fish Protectionmentioning
confidence: 82%
“…Evidence is also accumulating that the intake of EPA and DHA may influence cognitive function in the elderly. In the Zutphen Elderly Study, van Gelder et al (2007) examined fish consumption in 210 males, aged 70 to 89 years in 1990, along with estimates of cognitive function in 1990 and 1995. A significant (P , 0.01) positive linear trend was seen for the relationship between EPA 1 DHA intake and cognitive ability with a mean difference in intake of about 380 mg/day being associated with a 1.1-point difference in cognition.…”
Section: Lc N-3 Fatty Acids and Chronic Diseasementioning
confidence: 99%
“…A significant (P , 0.01) positive linear trend was seen for the relationship between EPA 1 DHA intake and cognitive ability with a mean difference in intake of about 380 mg/day being associated with a 1.1-point difference in cognition. van Gelder et al (2007) concluded that moderate intakes of EPA 1 DHA may delay the decline in cognitive function in elderly men. More recent studies have, however, not shown an association between EPA/DHA intake and long-term dementia risk (Devore et al, 2009;Krö ger et al, 2009).…”
Section: Lc N-3 Fatty Acids and Chronic Diseasementioning
confidence: 99%
“…A higher educational level and higher engagement in physical, cognitive and social activities are lifestyle factors that may reduce the risk of dementia or cognitive decline (Hamer and Chida 2009;Kareholt et al 2011;Morgan et al 2012;Niti et al 2008;Sattler et al 2012). Nutritional epidemiology has examined the potential benefit on cognition of fatty acids (van Gelder et al 2007), vitamins (Mangialasche et al 2010;Tangney et al 2009), fish (van Gelder et al 2007), fruit and vegetables (Hughes et al 2010) with favorable but not fully consistent results. Thus, both genetic and lifestyle-related factors are involved in cognitive decline and dementia, but these factors do not contribute independently to neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%